prove that overbar/(z1 + z2 + .... + zn) = overbar(z1) + overbar(z2) + .... +overbar(zn)

I showed true for n = 2 already

I then assumed true for n = k and wrote out the induction hypothesis

Then of course I need to show true for n = k + 1 and substitute the induction hypothesis in. So I came out with

overbar(z1 + z2 + .... + zn + zn+1) = overbar/(z1 + z2 + .... + zn) + overbar(zn+1)

I know I'm close, and I'm sure it's something simple that I'm missing but I don't know what to do next.

Any help?